A game-theoretic foundation for the Wilson equilibrium in competitive insurance markets with adverse selection - Wanda Mimra; Achim Wambach (Center for Economic Studies and ifo Institute (CESifo), 2011)
We extend the seminal Rothschild and Stiglitz (1976) model on competitive insurance markets with asymmetric information in the spirit of Wilson (1977)'s 'anticipatory equilibrium' by introducing an additional stage in which initial contracts can be withdrawn after observation of competitors' contract offers. We show that an equilibrium always exists where consumers obtain their respective Wilson-Miyazaki-Spence (WMS) contract. Jointly profit-making contracts can also be sustained as equilibrium contracts. However, the secondbest efficient WMS allocation is the unique equilibrium allocation under entry.
Keywords: G15; F36; 330; casymmetric information; competitive insurance market; contract withdrawal; Versicherungsökonomik; Spieltheorie; Asymmetrische Information; Adverse Selection; Vertrag; Gleichgewicht; Theorie